Analysis of safety characteristics of flight situation in complex low-altitude airspace - Zhongye Wang; Honghai Zhang; Minghua Hu; Qilun Qiu; Hao Liu (Advances in Mechanical Engineering, 2018)
This article studies on the analysis of safety characteristics of flight situation in complex low-altitude airspace with Agent-based simulation. Several aircraft behavior models are proposed taking account of complex low-altitude environment and general aviation flight characteristics, including an individual aircraft behavior model, a multi-flight behavior model, and an individual interaction model. And, some flight situation indicators are introduced to be used to analyze safety characteristics, such as flight volume, average speed, and flight conflict. In addition, a mixed flight situation simulation environment for complex low-altitude airspace is built with Agent technology and NetLogo. Based on the simulation environment, the relationship and influence rules among these flight situation indicators are found with flight situation evolution process. The results show a non-linear relationship between flight volume and flight conflict and conflict time; as flight volume increases, the fluctuation of average separation decreases, while the average speed-change increases first, but decreases with continuous increase in the volume, meanwhile the average heading-change gradually stabilizes after initial increase. It is also found that a reasonable setting of flight parameters is beneficial for the smooth operation of low-altitude airspace.